Race, consanguinity and social features in Birmingham babies: a basis for prospective study. Issue 2 (June 1990) - Bundey, S; Alam, H; Kaur, A; Mir, S; Lancashire, R J
Abstract : STUDY OBJECTIVE–The aim of the study was to investigate the influence of consanguinity on children's health. DESIGN–The study is a prospective survey from birth to five years of a cohort of babies born in a multiracial community. This report details the initial findings on consanguinity. SETTING–Participating families live predominantly in three health districts of Birmingham, and were recruited in three local maternity hospitals. PARTICIPANTS–Babies of 2432 European mothers, 509 Afro-Caribbean mothers, 625 Indian mothers, 956 Pakistani mothers, and 216 Bangladeshi mothers have been enrolled in the study. Eighty mothers refused to participate. MEASUREMENTS AND RESULTS–Sociodemographic information was obtained using a structured questionnaire administered at interview. Interview data were supplemented with obstetric information from the medical records. The highest prevalence of parental consanguinity was in Pakistani Muslims (69%), whereas in Muslims from other countries it was 23%, and it was less than 1% in non-Muslims. In the majority of consanguineous Muslim pedigrees the degree of inbreeding was greater than that for first cousin parents. CONCLUSIONS–This prospective study will allow an assessment to be made about any ill health in childhood arising from parental consanguinity, about whether screening programmes are indicated for particular autosomal recessive diseases, and about whether premarital health education might be beneficial. The study has also documented parental ages in different races and this, together with the levels of parental consanguinity in all races, will be useful in genetic methods for assessing the frequency of recessive genes, the possibility of genetic heterogeneity, and whether or not parental age effect exists for new mutations of specific genetic disorders.